1997
DOI: 10.1046/j.1365-2885.1997.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary effects of clonidine, diazepam and the peripheral α2 adrenoceptor agonist ST‐91 in conscious sheep

Abstract: The cardiopulmonary effects of the intravenous administration of clonidine (15 micrograms/kg), ST-91 (30 micrograms/kg) and diazepam (0.4 mg/kg) were compared in five healthy sheep using a randomized cross-over design, to determine whether the hypoxaemic effects of alpha 2 adrenoceptor agonists are due to sedation, or to peripheral alpha 2 adrenoceptor stimulation. All three drugs significantly lowered arterial oxygen tension (PaO2) levels within 2 min of their administration; however, clonidine and ST-91 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Lung oedema has been demonstrated in sheep following the administration of alpha2 agonists [3][4][5] . Lung oedema has not been demonstrated in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Lung oedema has been demonstrated in sheep following the administration of alpha2 agonists [3][4][5] . Lung oedema has not been demonstrated in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Different α 2 ‐agonists are known to induce hypoxaemia in sheep and cattle and the mechanism by which this effect occurs has been investigated in sheep by Celly et al . (1997a ), who found that both central and peripheral mechanisms were involved.…”
Section: Discussionmentioning
confidence: 99%
“…The heart rate decreased by 35% immediately after IV injection, but was attenuated and delayed after intrathecal and extradural administration (Castro & Eisenach 1989). An IV dose of 15 μ g kg −1 increased mean arterial blood pressure 30% within 2 minutes of injection and produced a prolonged decrease in heart rate (Celly et al. 1997a).…”
Section: Clonidine [2‐(26‐dichlorophenylamino)‐2‐imidazoline]mentioning
confidence: 99%
“…This α 2 ‐agonist has no central nervous activity and is used mainly in experimental studies as a model drug. When given to conscious sheep (30 μ g kg −1 IV) ST‐91 caused massive increases in arterial blood pressure and heart rate but did not produce sedation (Celly et al. 1997a).…”
Section: St‐91 [2(26‐diethylphenylamino)‐2‐imidazoline]mentioning
confidence: 99%
See 1 more Smart Citation